Photocatalytic activity of nanocrystalline TiNb2O7 obtained by a colloidal sol-gel route. Issue 6 (15th April 2018) - Falk, G.S.; Borlaf, M.; López-Muñoz, M.J.; Rodrigues Neto, J.B.; Moreno, R.
Abstract: Nowadays, TiO2 and Nb2 O5 are two of the most popular oxides in the field of photocatalysis due to their high activity. Their synthesis and their study not only separately, but also mixing them and their possibility to form other compounds like TiNb2 O7 are attracting the attention of different research groups. In this work, a detailed study of a colloidal sol–gel synthesis for obtaining nanoparticulate TiO2 :Nb2 O5 sols was performed. Amorphous nanoparticles with an average size of 10 nm were obtained by controlling the synthesis variables. After calcination of the xerogels at temperatures between 500 and 800 °C, different crystalline phases were obtained. Monoclinic TiNb2 O7 was the major phase and showed the highest photocatalytic activity.